Levels of Germinable Seed in Topsoil and Yak Dung on an Alpine Meadow on the North-East Qinghai-Tibetan Plateau - Xiao-jun YU; Chang-lin XU; Fang WANG; Zhan-huan SHANG; Rui-jun LONG (Journal of Integrative Agriculture, 2013)
In order to clarify the interactive mechanism between grazing yak and alpine meadow on the Qinghai-Tibetan Plateau, our study assessed seed density (by species) in the topsoil of alpine meadow with different grazing intensities in the Tianzhu area, north-eastern margins of the Qinghai-Tibetan Plateau and their rates of occurrence in yak dung. Seed density in the topsoil of the lightly grazed, moderately grazed, heavily grazed and extremely grazed alpine meadows in November, 2010 were 1551, 1692, 2660 and 1830 grains m−2, while in the same meadows in April, 2011 densities were 1530, 2404, 2530 and 2692 grains m−2, respectively. In the cold season pasture, mean seed density in yak dung from November to April in the lightly grazed, moderately grazed, heavily grazed and extremely grazed sites were 121, 127, 187, and 120 grains kg−1 of dry yak dung. The proportion of total seed numbers in yak dung to soil seed bank in lightly grazed, moderately grazed, heavily grazed and extremely grazed alpine meadow was 1.40, 2.62, 0.69, and 0.90%. 12 species out of the 47 were not found in topsoil but were found in yak dung, 10 species out of 45 were not found in yak dung but were found in the topsoil. Endozoochorous dispersal by yaks is therefore very important for soil seed bank and plant biodiversity and population dynamics in alpine meadows.